Effects on teaching listening skills through videos to advanced students from the foreign language Departament at the University of El Salvador during the first semester 2010 - Guzmán Martínez, Rolando,
In the Salvadoram education system, English is used as a foreign languaje and still complicated problem. Despite years of instruction, starting from junior hig school: seventh grade, many salvadoran cannot speak or understand simple english. A lack of proficient taching and suitable methods, including teaching tools are the important obstacles in teaching english. Every teachers knows those problems well. Therefore, in this paper, the researcher intends to help students to succeed in listening abilities, and provide new strategies, techniques and material for improving their listening skill and facilitating their learning. The purpose of this study was to examine the effectiveness of teaching EFL listening trough videos. The findings seggest that videos are helpful for students listenin improvement. english. Every teacher knows those problems